LPS Induces mTORC1 and mTORC2 Activation During Monocyte Adhesion - Ribeiro, Marcelle C.; Peruchetti, Diogo B.; Silva, Leandro S.; Silva-Filho, João L.; Souza, Mariana C.; Henriques, Maria das Graças; Caruso-Neves, Celso; Pinheiro, Ana Acacia S. (Frontiers in Molecular Biosciences, 2018)
Monocyte adhesion is a crucial step in transmigration and can be induced by lipopolysaccharide (LPS). Here, we studied the role of mammalian target of rapamycin (mTOR) complexes, mTORC1 and mTORC2, and PKC in this process. We used THP-1 cells, a human monocytic cell line, to investigate monocyte adhesion under static and flow conditions. We observed that 1.0 µg/mL LPS increased PI3K/mTORC2 pathway and PKC activity after 1 h of incubation. WYE-354 10-6 M (mTORC2/mTORC1 inhibitor) and 10-6 M wortmannin avoided monocyte adhesion in culture plates. In addition, WYE also blocked LPS-induced CD11a expression. Interestingly, rapamycin and WYE-354 blocked both LPS-induced monocyte adhesion in a cell monolayer and actin cytoskeleton rearrangement, confirming mTORC1 involvement in this process. Once activated, PKC activates mTORC1/S6K pathway in a similar effect observed to LPS. Activation of the mTORC1/S6K pathway was attenuated by 10-6 M U0126, an MEK/ERK inhibitor, and 10-6 M calphostin C, a PKC inhibitor, indicating that the MEK/ERK/TSC2 axis acts as a mediator. In agreement, 80 nM PMA (a PKC activator) mimicked the effect of LPS on the activation of the MEK/ERK/TSC2/mTORC1/S6K pathway, monocyte adhesion to ECV cells and actin cytoskeleton rearrangement. Our findings show that LPS induces activation of mTOR complexes. This signaling pathway led to integrin expression and cytoskeleton rearrangement resulting in monocyte adhesion. These results describe a new molecular mechanism involved in monocyte adhesion in immune-based diseases.